Study on the Perception and attitude toward influence of the internet advertising on social media - Chang, Chee Yoong; Othman, Zakirah (Universiti Utara Malaysia, 2020)
Generally, social media is the one of the new trends in information and communication technology and huge market. Social media is a suitable place to do advertise product or idea because this platform has a huge user and can target right people. From this study, the objective is to investigate the relationship between internet advertisements on social media and what expertise perception on SRI-Mas Facebook in promote quality internet advertising. In this study have been used qualitative method to collection data to identify the perception and attitude user toward influence internet advertising on social media from the interview and observation technique. Advertising is a form of communication that provides useful and relevant information to viewers for immediate action or use at the time of purchase. The result demonstrate social media is very effective and expected attention. It is a new trend of advertising nowadays.